End-of-life preferences of the general public: Results from a Japanese national survey. Issue 11 (November 2015) - Kissane, Lee Andrew; Ikeda, Baku; Akizuki, Reiko; Nozaki, Shoko; Yoshimura, Kimio; Ikegami, Naoki
Highlights: The proportion wanting to spend EoL in hospital is higher than at home in Japan. At EoL hospital is preferred for cancer and cardiac failure; care home for dementia. At EoL many want IVs and antibiotics but few want NG, PEG, ventilation and CPR. Preferences for LST and EoL setting are associated for cancer and cardiac failure. Preferences for LST and EoL care setting are not associated in dementia. Abstract: Purpose: To determine under different End-of-Life (EoL) scenarios the preferences of the general public for EoL care setting and Life-sustaining-Treatments (LST), and to develop a new framework to assess these preferences. Method: Using a 2-stage, geographical cluster sampling method, we conducted a postal survey across Japan of 2000 adults, aged 20+. Four EoL scenarios were used: cancer, cardiac failure, dementia and persistent vegetative state (PVS). Results: We received 969 valid responses (response rate 48.5%). Preference for EoL care setting varied by illness with those wishing to spend EoL at home only 39% for cancer, 22% for cardiac failure, and 10–11% for dementia and PVS. Preference for LST differed by scenario and treatment type. In cancer, cardiac failure and dementia, about half to two thirds expressed a preference for antibiotics and fluid drip infusion but few for nasogastric (NG) tube feeding, percutaneous endoscopic gastrostomy (PEG), ventilation or cardiopulmonary resuscitation (CPR). Although our models accounted for only 3–9% of the variance, preferences to receive LST were associated with preference to spend EoL in hospital for cancer and cardiac failure but not dementia. Conclusions: Few people preferred to die at home, while a preference for hospital was largely determined by factors other than preference for LST.